Avaliação das condições de saúde e segurança de trabalho dos profissionais da saúde em unidades hospitalares públicas do Ceará na Pandemia de Covid-19 - Silva, Márcia Maria Araújo da (2023)
The health and safety of health workers in Brazil became widely debated with the advent of the COVID-19 pandemic, promoting visibility to the problems experienced daily by these professionals in their work context. Labor legislation and Regulatory Norms (NR's), issued by the Ministry of Labor regulate the requirements and procedures related to the health and safety of employees in the work environment. However, labor provisions differ when workers are under the Consolidation of Labor Laws (CLT) regime and their own legal regime (federal, municipal or state). The objective was to evaluate the working conditions to which health professionals are exposed in the context of the COVID-19 pandemic. It was an exploratory and descriptive research, with a quantitative and qualitative approach and included a bibliographical review with documental analysis in addition to field research carried out with health professionals with different employment links allocated in three public hospital institutions at the federal and municipal levels in Fortaleza- Ceará, through an interview and questionnaire from May to July 2022. Quantitative data were compiled through the Research Electronic Data Capture (REDCAP) platform and analyzed according to descriptive statistical tests, absolute and relative frequencies, means and standard deviations. For the analysis of qualitative data, the discourse analysis technique was used, applying Minayo's method triangulation as a theoretical reference. This research was approved by the Research Ethics Committee of the three institutions. The results showed that most professionals were women aged between 22 and 59 years (98.8%), stable marital status (61.5%), complete postgraduate studies (43.4%), although performing professional activities such as middle level. Most were from the nursing area: 66.3% were technicians and 19.3% were nurses, with between 21 and 30 years in the profession (48.2%). Regarding comorbidities, the most cited were related to the cardiovascular (21.7%) and endocrine (13.2%) systems. With regard to personal perception as a health professional in the context of the pandemic, the most cited feeling was fear, including quotes about the possibility of bringing contamination to family members. Regarding the restructuring of the hospital units studied for the care of cases of respiratory syndromes, 43.3% of the participants agreed on this aspect, especially regarding the physical environment, however, when checking the issue of training the team to care for patients with COVID -19, 46.9% disagreed that they felt prepared; another 42.1% emphasized that there was not enough personal protective equipment. The COVID-19 pandemic showed that the impacts on health services went beyond the infrastructural, physical field and intertwined with the needs of workers, since, even with current legislation, actions to protect the health and safety of professionals of health, regardless of their employment relationship, was not enough to meet the demand of this professional during the current pandemic period.